Integrasi Nilai Budaya Siriâdan Pesse/Pacce Masyarakat Bugis-Makassar Dalam Pembelajaran IPA - Rahmawati, Rahmawati (Office of International Affairs (OIA), 2015)
The value of siriâ and pesse/pacce that is the philosophy and principles of life in South Sulawesi Bugis-Makassar community contains so sacred meaning if it is pursued and functioned in a positive direction. One of these efforts can be investigated in how teachersâ involvement that has dynamic magnitude to integrate cultural values of siriâ and pesse into learning science as an effort to create an atmosphere and environment that is conducive to learning science and based on local wisdom. There are relationship between concepts of hands-on and minds-on in learning science and cultural value of siriâ and pesse so that cultural values can be integrated into teaching science.Keywordsâ Value of Siriâ Culture, Principle of Buginese & Macassare, Local Wisdom, Learning Science.